Enhancing Educational Management through Social Media and E-commerce-Driven Branding - Susy Alestriani Sibagariang; Nanda Septiani; Anthony Rodriguez (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
Intensified digital competition is forcing organizations across diverse sectors, from the B2B carton box industry to Educational Management, to seek differentiation through strategic digital branding. This is particularly true for industrial firms often trapped by commoditization. However, existing literature frequently analyzes social media and e-commerce in silos, creating a research gap regarding their synergistic impact on internal management. This study aims to fill this gap by empirically validating a holistic model that links the strategic integration of these digital platforms to brand enhancement, management quality, and sustainable competitive advantage. The novelty of this research lies in demonstrating this complete causal pathway within an industrial B2B context, offering a transferable framework for other fields. Using a quantitative approach, survey data from 150 respondents in the carton box industry were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results confirmed all five hypotheses, revealing that strategic integration is an exceptionally strong predictor of brand enhancement (β = 0.979). The findings cruciallydemonstrate that brand enhancement is the primary mediating variable; its effect on improving management quality and securing a competitive advantage is substantially stronger than other direct paths. This study concludes that the most effective mechanism for organizations, industrial companies, or institutions in educational management, to achieve market leadership in the digital era is by strategically using integrated digital tools to first cultivate a powerful and trusted brand.